Efeitos do exercício excêntrico na reabilitação do músculo esquelético de camundongos mdx após 3 e 21 dias de treinamento. Avaliações morfológica, funcional e molecular - Pedrazzani, Paulo Silva (Universidade Federal de São Carlos, 2019)
Duchenne Muscular Dystrophy (DMD) is a degenerative genetic disease of a recessive nature linked to the mutation of the Xp21 region of the X chromosome. DMD is characterized by the absence of the protein dystrophin, which causes progressive muscle degeneration and weakness, resulting in death of the patient due to respiratory failure and or cardiac. Changes in the content of the myosin heavy chain (MHC) are commonly observed in dystrophic muscles and may be related to the greater fragility of this tissue. Because it is a progressive and disabling disease, physiotherapeutic resources such as physical exercise are commonly used to provide greater comfort for patients during disease progression. However, the major limitation is to determine the type and intensity of the exercise to be applied. For some time, eccentric exercise has been used in the rehabilitation of skeletal muscle after disuse, in the same way, studies show its effectiveness in the rehabilitation of dystrophic muscles, however, there are few reports in the scientific literature on the cellular and involved in the regeneration process. Therefore, the objective of this study is to analyze the molecular processes involved in the destruction of myofibers of mdx animals and to evaluate the consequences of the application of low intensity eccentric training for 21 days in the cytoarchitecture and in the contractile function of myofibers. Methods: Male mice aged 6 weeks, divided into 8 groups: sedentary mdx 3 days (mdxSED3) and sedentary mdx 21 days (mdxSED21) were used in this study; mdx trained 3 and 21 days, mdxTR3 and mdxTR21, respectively; wild type sedentary 3 and 21 days (wtSED3 and wtSED21) and finally, wild type trained 3 (wtTR3) and 21 days (wtTR21). After the training periods the animals were euthanized and blood samples were obtained for analysis of the enzyme creatine kinase (CK). Afterwards, both of the muscles were excised and subjected to functional analysis, for single fiber contraction force; morphology, for general aspects of the tissues; and morphometry, for the proportion of different types of fibers and tropism. Results: The single fiber strength analysis of the mdx mice showed a significant reduction when compared to the control group. In the morphological analysis it was possible to observe important alterations determined by the disease, such as: necrosis, increased connective tissue, nuclear centralization, among others. In the proportion of fibers, the dystrophic muscles presented a reduction in the number of types IIA fibers (FTIIA) concomitant to the increase of type I fibers (FTI), when compared to the respective controls. For trophic analysis, all types of fibers were observed in the youngest dystrophic group (3 days) while the oldest group (21 days) had a reduction in FTI and FTIIA fibers. After application of the low intensity eccentric training, it was possible to observe in the dystrophic muscles that the application of the exercise for 21 days was more effective in almost all aspects analyzed when compared to the more acute time (3 days). Conclusion: Our results suggest that eccentric exercise when applied at a low intensity for a longer period may be an effective therapeutic strategy to improve the functional, morphological and biochemical changes determined by the absence of the protein dystrophin.
Effects of eccentric exercise in rehab of the mdx muscle rehab after 3 and 21 days of training. Morphological evaluations, functional and molecular
Keywords: Enzima creatina quinase.; Trofismo; Proporção dos diferentes tipos de fibras; Fibra única.; Exercício excêntrico; Camundongos mdx; Distrofia muscular de Duchenne; Creatine kinase enzyme; Tropism; Proportion of different fiber types; Single fiber; Eccentric exercise; mdx mice; Duchenne muscular dystrophy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL